THU0317 Creating a european database of psoriatic arthritis patients treated in routine care – first, preliminary results from the eurospa research network collaboration. (12th June 2018) - Ørnbjerg, L.M.; Østergaard, M.; Onen, F.; Birlik, M.; Rotar, Z.; Tomsic, M.; Gudbjornsson, B.; Love, T.J.; Nissen, M.J.; Ciurea, A.; Nordström, D.; Trokovic, N.; et al.
Abstract : Background: A research network collaboration of 15 European registries collecting data on patients with spondyloarthitis (SpA), "EuroSpA", has recently been created to strengthen research capabilities in the real world setting 1 . Here we present initial findings from the collaboration. Objectives: To investigate the feasibility of creating a common database within the EuroSpA collaboration and to conduct proof-of-concept analyses by investigation of baseline characteristics, disease activity at baseline and after 6 months and 12 months' TNFi retention rate in patients with psoriatic arthritis (PsA) initiating Tumour Necrosis Factor inhibitors (TNFi). Methods: A common data model for PsA was agreed upon by the EuroSpA Scientific Committee. Virtual meetings between the EuroSpA and registry data managers clarified data availability and structure. This was followed by upload of anonymized data through the secure Virtual Private Network pipelines to the EuroSpA server. Baseline characteristics and disease activity at baseline and after 6 months were investigated with non-parametric descriptive statistics. Kaplan-Meier estimation was used to investigate TNFi retention rates. Results: : By January 8th 2018, four of the 15 registries participating in EuroSpA had completed data upload to the EuroSpA database resulting in 3172 patients with PsA in a pooled dataset. Baseline characteristics of the participating registry populations at initiation of first TNFi are shown in table 1. Crude 12 month TNFi retention rates varied from 65%–80% for 1st TNFi and 57%–82% for 2nd TNFi (see figure 1). For the pooled dataset crude 12 months TNFi retention rates were 68% and 60% for the 1st and 2nd TNFi, respectively. Conclusions: Preliminary analyses showed differences across European registries regarding baseline characteristics and crude retention rates in PsA patients initiating TNFi. These initial, preliminary analyses demonstrate that the creation of a large European database of PsA patients treated in routine care based on a common data model is feasible, offering important opportunities for future research. Reference: [1] Ann Rheum Dis2017;2:65. Acknowledgements: The authors acknowledge Novartis Pharmaceuticals AG for financial support and Natasha Pillai and Carol Lines from QuintilesIMS and Craig Richardson from Novartis Pharmaceuticals AG for their assistance in setting up the EuroSpA collaboration. Disclosure of Interest: L. Ørnbjerg: None declared, M. Østergaard: None declared, F. Onen: None declared, M. Birlik: None declared, Z. Rotar: None declared, M. Tomsic Consultant for: AbbVie, Eli Lilly, Johnson and Johnson, Medis, MSD, Novartis, Pfizer and Roche, B. Gudbjornsson: None declared, T. Love: None declared, M. J. Nissen: None declared, A. Ciurea: None declared, D. Nordström Consultant for: AbbVie, Celgene, BMS, Lilly, MSD, Novartis, Pfizer, UCB, N. Trokovic: None declared, M. Santos: None declared, A. Barcelos: None declared, E. Kristianslund: None declared, T. Kvien Grant/research support from: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celgene, Celltrion, Eli Lilly, Epirus, Hospira, Merck-Serono, MSD, Mundipharma, Novartis, Orion Pharma, Hospira/Pfizer, Sandoz, UCB, C. Codreanu: None declared, E.-M. Hauge: None declared, J. Askling: None declared, F. Iannone: None declared, H. Mann: None declared, M. V. Hernandez: None declared, G. Macfarlane: None declared, M. van de Sande: None declared, L. H. Hyldstrup: None declared, N. S. Krogh: None declared, M. Hetland Grant/research support from: AbbVie, Biogen, BMS, CellTrion, MSD, Orion, Pfizer, Samsung, UCB